The Interplay between Asthma, Obesity, and Obstructive Sleep Apnea - Rodriguez, Lucia R.; Sharma, Sunita (Seminars in Respiratory and Critical Care Medicine, 2025)
The interrelationship between asthma, obesity, and obstructive sleep apnea (OSA) presents a critical area of investigation within sleep medicine, given the rising prevalence of these conditions globally. This article explores the multifactorial interactions among these three disorders that contribute to significant morbidity. Asthma, a chronic inflammatory condition of the airways, is one of the most common chronic respiratory conditions globally. Asthma in people with obesity is associated with poor asthma control, increased asthma severity, and an increased frequency of exacerbations. Obesity, characterized by excessive fat accumulation, is a well-established risk factor for the development of OSA. This sleep-related breathing disorder disrupts airflow during sleep due to pharyngeal collapse. Conversely, OSA may worsen asthma symptoms through intermittent hypoxia and sleep fragmentation, further complicating asthma management. This review analyzes existing literature to illustrate the bidirectional relationships among these conditions. It discusses the role of systemic inflammation, hormone dysregulation, and lifestyle factors, such as diet and physical inactivity, in the development and persistence of asthma and OSA in obese patients. Furthermore, it highlights the importance of comprehensive management strategies that address these overlapping disorders. Clinical implications are examined, with consideration given to the potential for targeted therapies and lifestyle interventions that could mitigate symptoms and improve the quality of life for affected individuals. Understanding these complex interactions is essential for healthcare practitioners in optimizing the management of patients with asthma, obesity, and OSA. By recognizing the interconnectedness of these conditions, clinicians can adopt a more holistic approach to treatment, leading to improved outcomes and a better understanding of the patient's overall health trajectory. Future research directions are suggested to investigate potential therapeutic interventions and the influence of socioeconomic factors on these chronic conditions.
Keywords: asthma; obesity; obstructive sleep apnea; inflammation; comorbidities; metabolic dysfunction